Accurate large scale modelling of graphene oxide: Ion trapping and chaotropic potential at the interface. (15th April 2021) - al-Badri, Mohamed Ali; Smith, Paul; Sinclair, Robert C.; al-Jamal, Khuloud T.; Lorenz, Christian D.
Abstract: Graphene oxide (GO) shares many novel mechanical and electronic properties with graphene and has been applied extensively for uses in physics, engineering and medicine. Computational simulations of GO have widely neglected accurate characterisation by random functionalisation, forsaking steric strain and abandoning edge functional groups. Here, we show that molecular dynamics forcefield design using electronic structure calculations of hundreds of atoms of GO with accurate functionalisation shows good agreement with state-of-the-art ab initio molecular dynamics (AIMD) simulations. We find that the bespoke forcefield shows better agreement with previous AIMD and experimental results in terms of the interfacial water dynamics and ion adsorption. Namely, GO described by the bespoke forcefield is found to disrupt the hydrogen bonding network at the interface by playing a more dynamic role in accepting and donating hydrogen bonds from water. Furthermore, with the bespoke forcefield, we find preferential adsorption of ions to carboxyl functional groups and a similar mean adsorption half-life for Na + and Cl − ions around GO. These findings are critical for future investigations of GO in complex environments in application ranging from desalination to protein adsorption for drug delivery. Graphical abstract: Image 1